Role and management of soil biodiversity for food security and nutrition; where do we stand? - El Mujtar, Veronica Andrea (2019)
Soils host diverse communities that support and regulate ecosystem functions, thereby affecting plant production and resource use efficiencies. There is increasing evidence that agricultural intensification affects soil biodiversity (SBD) and such changes may impact on current and future food security. Here, we provide an overview of the state-of-the-art on the relations between agricultural management, SBD and food production. The potential of applying such knowledge to improve food security and nutrition is discussed. Biotechnological methods to describe impacts of agricultural practices on taxonomic and functional diversity of soil organisms are advancing rapidly. At the same time new understanding of soil-plant interactions has provided novel insights into the mechanisms by which soil organisms and plants co-regulate plant growth and defences, or affect food nutritional quality and safety. Yet, empirical studies on SBD – plant productivity relations often lead to results and applications that are crop and context specific. Translating knowledge on SBD into universally applicable soil management recommendations to enhance food production, and ultimately food security, remains challenging. Instead, we propose a holistic approach to SBD management that strengthens multiple ecosystem functions and provides ecological insurance.